Prenylated chalcone 2 ccts as an antimitotic agent and enhances the chemosensitivity of tumor cells to paclitaxel - Fonseca, Joana (2017)
We previously reported that prenylated chalcone 2 (PC2), the O-prenyl derivative (2) of 2'-hydroxy-3,4,4',5,6'-pentamethoxychalcone (1), induced cytotoxicity of tumor cells via disruption of p53-MDM2 interaction. However, the cellular changes through which PC2 exerts its cytotoxic activity and its antitumor potential, remain to be addressed. In the present work, we aimed to (i) characterize the effect of PC2 on mitotic progression and the underlying mechanism; and to (ii) explore this information to evaluate its ability to sensitize tumor cells to paclitaxel in a combination regimen. PC2 was able to arrest breast adenocarcinoma MCF-7 and non-small cell lung cancer NCI-H460 cells in mitosis. All mitosis-arrested cells showed collapsed mitotic spindles with randomly distributed chromosomes, and activated spindle assembly checkpoint. Live-cell imaging revealed that the compound induced a prolonged delay (up to 14 h) in mitosis, culminating in massive cell death by blebbing. Importantly, PC2 in combination with paclitaxel enhanced the effect on cell growth inhibition as determined by cell viability and proliferation assays. Our findings demonstrate that the cytotoxicity induced by PC2 is mediated through antimitotic activity as a result of mitotic spindle damage. The enhancement effects of PC2 on chemosensitivity of cancer cells to paclitaxel encourage further validation of the clinical potential of this combination.